Correlation between estimated glucose disposal rate, insulin resistance, and cardiovascular mortality among individuals with metabolic syndrome: a population-based analysis, evidence from NHANES 1999–2018 - Dawei Xing; Jing Xu; Xiaochun Weng; Xiaolu Weng (Diabetology & Metabolic Syndrome)
Abstract Background Estimated glucose disposal rate (eGDR), is an index of insulin resistance. It is intimately correlated with inflammation and endothelial dysfunction, both of which are contributory factors in the pathogenesis of cardiovascular disease (CVD) and premature mortality. This study aims to explore the correlation between eGDR and both all-cause and CVD-related mortality in adults with metabolic syndrome (MetS). Methods A total of 8215 subjects with MetS screened from the National Health and Nutrition Examination Survey (NHANES) during the period from 1999 to 2018 were evaluated for the predictive value of eGDR for CVD and all-cause mortality. Results Over a median follow-up for 8.3 years, a total of 1537 all-cause deaths (18.7%) and 467 CVD-related deaths (5.7%) were recorded. Logistic regression analyses revealed a significant inverse correlation between eGDR and the risk of having CVD (OR:0.845, 95%CI:0.807–0.884, p < 0.01). Multivariate Cox regression analysis and restricted cubic splines analysis demonstrated that eGDR is non-linearly correlated with both the mortality of CVD (HR: 0.906, 95% CI: 0.850–0.967, p = 0.003) and all-cause mortality (HR: 0.944, 95% CI: 0.912–0.977, p = 0.001), with an identified inflection point at 5.918. Further subgroup analyses indicated a more pronounced correlation between eGDR and all-cause mortality in individuals under 60 years old (HR: 0.893, 95%CI:0.823–0.970) or those with obesity (HR:0.891, 95%CI:0.839–0.946). Mediation analysis revealed that neutrophil to lymphocyte ratio mediated 8.9% of the correlation between eGDR and all-cause mortality. Conclusion This study demonstrates, for the first time, that a decrease in eGDR is associated with an increased risk of all-cause and CVD mortality in adults with MetS. The eGDR indices could serve as surrogate biomarkers for monitoring patients with MetS.